2023
DOI: 10.1093/ejcts/ezad230
|View full text |Cite
|
Sign up to set email alerts
|

The impact of resource allocation during the COVID-19 pandemic on cardiac surgical practice and patient outcomes: a systematic review

Abstract: OBJECTIVES The COVID-19 pandemic has shaken the world and placed enormous strain on healthcare systems globally. In this systematic review, we investigate the effect of resource allocation on cardiac surgery programs and the impact on patients awaiting elective cardiac surgery. METHODS PubMed and Embase were systematically searched for articles published from January 1st 2019-August 30th 2022. This systematic review included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…A substantial body of literature has demonstrated a dramatic drop in admissions of patients with coronary syndrome [6-8] and adult cardiac surgery volume [9][10][11][12] following the outbreak of COVID-19 pandemic, resulting in backlogs of cases awaiting cardiac surgery [5,23]. In line with previous studies, the pandemic onset was also associated with an immediate sharp decline of adult cardiac surgery volume (percentage change: 54•80%, 95% CI:…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…A substantial body of literature has demonstrated a dramatic drop in admissions of patients with coronary syndrome [6-8] and adult cardiac surgery volume [9][10][11][12] following the outbreak of COVID-19 pandemic, resulting in backlogs of cases awaiting cardiac surgery [5,23]. In line with previous studies, the pandemic onset was also associated with an immediate sharp decline of adult cardiac surgery volume (percentage change: 54•80%, 95% CI:…”
Section: Discussionmentioning
confidence: 60%
“…It has been reported that the pandemic was associated with a greater risk of morbidity and mortality [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations